2018
DOI: 10.3390/v10100573
|View full text |Cite
|
Sign up to set email alerts
|

βTrCP is Required for HIV-1 Vpu Modulation of CD4, GaLV Env, and BST-2/Tetherin

Abstract: The Human immunodeficiency virus-1 (HIV-1) accessory protein Vpu modulates numerous proteins, including the host proteins CD4 and BST-2/tetherin. Vpu interacts with the Skp, Cullin, F-Box (SCF) ubiquitin ligase through interactions with the F-Box protein βTrCP (1 and/or 2). This interaction is dependent on phosphorylation of S52,56 in Vpu. Mutation of S52,56, or inhibition of the SCF, abolishes most Vpu activity against CD4 and partly reduces activity against BST-2/tetherin. Recently, Vpu has also been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 56 publications
(108 reference statements)
0
19
0
Order By: Relevance
“…Phosphorylation of the serine residues of this motif allows the recruitment of the β-TrCP subunit of the SCF β-TrCP1/2 E3 ubiquitin ligase complex, leading to the ubiquitination and degradation of BST-2 in lysosomes (20, 21). Increasing evidence suggests that the recruitment of β-TrCP and the degradation of BST-2 by Vpu are dissociable from its ability to antagonize BST-2 (11, 14, 15, 18, 19, 22), although this is subject to debate (23).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of the serine residues of this motif allows the recruitment of the β-TrCP subunit of the SCF β-TrCP1/2 E3 ubiquitin ligase complex, leading to the ubiquitination and degradation of BST-2 in lysosomes (20, 21). Increasing evidence suggests that the recruitment of β-TrCP and the degradation of BST-2 by Vpu are dissociable from its ability to antagonize BST-2 (11, 14, 15, 18, 19, 22), although this is subject to debate (23).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated the mechanism behind virus-specific incompatibility dependent on the Env CT. The GaLV Env CT incompatibility with HIV-1 has been extensively studied, and we along with others reported that the incompatibility was partly dependent on Vpu (8,20,25,26,44,45). Here, we addressed the GaLV Env CT incompatibility remaining in the absence of Vpu.…”
Section: Discussionmentioning
confidence: 97%
“…HIV-1 accessory protein Vpu is well known to promote virus release from infected cells. Recent studies indicate that Vpu recruits tetherin, CD4, or P-selectin glycoprotein ligand 1 (PSGL-1) to CRL1 substrate receptor b-TRCP for ubiquitination and degradation [182,183]. Transmembrane protein tetherin functions as a tether between nascent virions and infected cells, as well as between nascent virions.…”
Section: Neddylation and Viral Infectionmentioning
confidence: 99%
“…It was shown to interact with tetherin through its transmembrane domain and with b-TRCP through its intracellular domain, followed by ubiquitination-induced endosomal degradation of tetherin [182,184]. Vpu targeted CD4 with its intracellular domain for ubiquitination and subsequent proteasomal degradation to avoid the re-adsorption of the nascent virions [182,183]. PSGL-1 is a transmembrane protein induced by IFN-c in activated CD4 + T cells.…”
Section: Neddylation and Viral Infectionmentioning
confidence: 99%